Democratization of Tomorrow's Plate: Synergizing Foresight Methods and Design Thinking in Designing Cellular Agriculture Innovations - Nhokovedzo, Simbarashe; Tapio, Petri; Witoon, Siyada; Uverov, Nikita; Mushayavanhu, Tawanda Prosper (Wiley, 2026)
This paper presents a sustainable design framework for cellular agriculture innovations by integrating foresight methods and design thinking. Importantly, the research connected design thinking, foresight methods and sustainable innovations. The framework systematically aligns foresight methods with the design thinking process, thus enabling cellular agriculture innovators to anticipate long-term challenges and navigate uncertainties. The strengths and limitations of either design thinking or foresight are explored thus rationalizing the need to integrate them. A key research question of the study is: How can foresight methods be systematically integrated with design thinking to enhance the sustainability of Cellular Agriculture innovations? A user-friendly framework is developed by matching foresight methods capabilities and aims of design thinking stages. The paper discusses theoretical and practical implications of the framework while pointing direction of further research in shaping sustainable food systems.